2013
DOI: 10.1007/s11356-013-1509-0
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of microcontaminants by crops irrigated with reclaimed water and groundwater under real field greenhouse conditions

Abstract: The use of reclaimed water for agricultural irrigation has emerged as a new strategy for coping with water scarcity in semiarid countries. However, the incorporation of the organic microcontaminants in such water into the diet through crop uptake poses a potential risk to human health. This paper aims to assess the presence of organic microcontaminants in different crops irrigated with groundwater and reclaimed water (secondary or tertiary effluents) in a greenhouse experiment. The determination of microcontam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…The Food and Drug Administration estimated that in 2012 more than 14.6 million kilograms of antimicrobial drugs were ibuprofen, levamisole, trimethoprim, and sulfamethazine) can enter vegetables and crops (e.g. carrot, lettuce, soybeans and alfalfa) from soil and water [1,5,[12][13][14]. Sabourin et al [15] reported that pharmaceuticals in the soils originating from fertilization with municipal biosolids at agronomic rates could be accumulated in tomato, carrot, potato or sweet corn with the concentrations ranging from 0.33 to 6.25 ng g −1 dry weight.…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration estimated that in 2012 more than 14.6 million kilograms of antimicrobial drugs were ibuprofen, levamisole, trimethoprim, and sulfamethazine) can enter vegetables and crops (e.g. carrot, lettuce, soybeans and alfalfa) from soil and water [1,5,[12][13][14]. Sabourin et al [15] reported that pharmaceuticals in the soils originating from fertilization with municipal biosolids at agronomic rates could be accumulated in tomato, carrot, potato or sweet corn with the concentrations ranging from 0.33 to 6.25 ng g −1 dry weight.…”
Section: Introductionmentioning
confidence: 99%
“…In the section addressing the accumulation of PPCPs in plants grown in soils that were irrigated with wastewater, only two studies were thoroughly discussed (Calderon-Preciado et al, 2013;Goldstein et al, 2014). Furthermore, the data do not properly describe PPCP uptake by plants under wastewater irrigation.…”
Section: Crop Growing Conditionsmentioning
confidence: 99%
“…Similarly, Jelic et al (2011) reported the presence of 29 PPCPs in effluent water in Spain. In studies that have examined the uptake of PPCPs by plants grown under field conditions, compounds have been applied as mixtures resulting in more than one PPCP being detected in a single crop (Wu et al, 2010(Wu et al, , 2012Calderon-Preciado et al, 2013;Goldstein et al, 2014;Malchi et al, 2014). Thus, the article conveys the impression of safety, with a de minimis risk, when ignoring that exposure to PPCPs is always as mixtures and not as single compounds.…”
Section: Metabolites Of Ppcpsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Some types of PPCPs can accumulate in the edible parts of crops, posing a significant threat to human health (e.g., disrupting human endocrine systems and inhibiting growth of human embryonic cells). 4,33,[35][36][37] In recent years, guidelines associated with PPCPs have been issued by the Europe Union, the United States, and other countries due to their potential environmental risks. 10, 21 Although the guidelines might be able to limit the environmental release of these chemicals, the effectiveness of the guidelines may fall short due to the lack of a systemic analysis of the occurrence, distribution, transformation, and mobility of various PPCPs and an assessment of their effects on an agro-system subject to reclaimed water irrigation.…”
Section: Introductionmentioning
confidence: 99%